Return of aboveground nutrients by switchgrass into the surrounding soil during senescence - Holou, Roland Ahouelete Yaovi; Stevens, Gene; Kindomihou, Valentin Missiakô (My University, 2013)
Background: Switchgrass (Panicum virgatum L.) is a crop that holds promise for cellulosic biofuel production. To minimize fertilizer costs, farmers prefer to reduce crop removal of nutrients from the soil when biomass is harvested. The objective of this study was to monitor, from May 2008–November 2009 at Portageville  (MO, USA), the nutrient concentration in the soil, switchgrass roots and rhizomes in a 20-year-old switchgrass field. Soil and tissue samples were collected to determine the sink of the nutrients lost in the aboveground biomass during senescence of the plant. Results: Nutrient concentration in switchgrass biomass decreased from July to the end of the season. In general, as switchgrass senesced, the nutrient concentration of the roots did not significantly change, whereas that of the rhizomes increased. Soil test results varied depending on where samples were collected relative to switchgrass root clumps. Generally, soil samples collected from the clump showed the highest evidence of nutrients returning to the soil from the aboveground biomass; however, some of this could be due to root breakage during sampling. Soil ammonium acetate extracted K in the clumps and averaged 218 kg K kg -1 soil in October, compared with 302 mg K kg -1 soil in November. Soil NO 3 -N content in the clumps in November was 5.5 mg kg -1 soil, compared with 1.5 mg kg -1 soil in October. Conclusion: This study provided evidence of nutrient recycling in the field by switchgrass plants and supports the concept of a reverse flow of nutrients to soil at the end of the season. The harvest of switchgrass late in November will help minimize the nutrient removal and maximize biomass yield.
Keywords: NH3; Volatilization; Rubisco; Necromass